2010
DOI: 10.1152/jn.00843.2009
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Control of Multisaccade Gaze Shifts During Movement Preparation and Execution

Abstract: Although the nature of gaze control regulating single saccades is relatively well documented, how such control is implemented to regulate multisaccade gaze shifts is not known. We used highly eccentric targets to elicit multisaccade gaze shifts and tested the ability of subjects to control the saccade sequence by presenting a second target on random trials. Their response allowed us to test the nature of control at many levels: before, during, and between saccades. Although the saccade sequence could be inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 73 publications
2
29
1
Order By: Relevance
“…Although we chose not to include such trials in our comparative analysis of antagonist neck muscle latency with SSRTs, because the GO process technically wins the race on such trials, the STOP process is still engaged to arrest the trial in mid-flight. While we note that other studies have reported truncated movements previously in other tasks (Boucher et al 2007b;Ramakrishnan et al 2010), we observed a much higher incidence in this study. Presumably, the use of larger amplitude gaze shifts (which last longer) provides more opportunity for mid-flight movement cancellation.…”
Section: Implications For the Study Of Countermandingcontrasting
confidence: 75%
See 1 more Smart Citation
“…Although we chose not to include such trials in our comparative analysis of antagonist neck muscle latency with SSRTs, because the GO process technically wins the race on such trials, the STOP process is still engaged to arrest the trial in mid-flight. While we note that other studies have reported truncated movements previously in other tasks (Boucher et al 2007b;Ramakrishnan et al 2010), we observed a much higher incidence in this study. Presumably, the use of larger amplitude gaze shifts (which last longer) provides more opportunity for mid-flight movement cancellation.…”
Section: Implications For the Study Of Countermandingcontrasting
confidence: 75%
“…This prolonged duration provides an interval in which subjects can cancel an on-going gaze shift in mid-flight. The presence of truncated gaze shifts suggest that gaze shifts are not completely ballistic (e.g., Ramakrishnan et al 2010) and that the processing of the stop signal continues after the initiation of the gaze shift. However, because we are explicitly interested in neck muscle recruitment as a function of the control of the gaze axis, we have derived our measures of antagonist muscle recruitment exclusively from trials with head-only errors to avoid confounds associated with gaze shift initiation.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Behavioral data were collected from 56 sessions (31 sessions from Monkey C and 25 sessions from Monkey D) while monkeys performed the redirect task (Ray et al, 2004;Ramakrishnan et al, 2010). In this task, monkeys made a quick saccade to the initial target as soon as it appeared (no-step trials; see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Monkeys were trained on the redirect task (Ray et al, 2004;Ramakrishnan et al, 2010), which is a modified version of the classic double-step task (Westheimer, 1954;Wheeless et al, 1966;Komoda et al, 1973;Lisberger et al, 1975;Becker and Jürgens, 1979;Aslin and Shea, 1987;Ray et al, 2004). The task consists of two kinds of trials: no-step trials, in which a single target is presented; and step trials, in which two targets are presented in succession.…”
Section: Behavioral Paradigmmentioning
confidence: 99%
See 1 more Smart Citation